Optimasi Waktu dan Biaya Proyek Flue Stack Menggunakan Metode Time Cost Trade Off - Balqis Rahmi Salsabil; Renanda Nia Rachmadita; Aulia Nadia Rachmat (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Abstract - Construction company in Karangpilang received an order for the Flue Stack project. There was a delay on this project, so the company has to pay a fine of 0,2% of the initial contract which is calculated everyday. Therefore, research is needed to analyze project scheduling so that optimal time and cost are obtained from working on the Flue Stack project. The methods used in this study are the Time Cost Trade Off method. Crashing is carried out on several critical activities, such as marking/cutting, roll, assembly ring, blasing/primer, assembly segment, finish painting, and packing. This research used an alternative to crashing with additional overtime and labor. The results of this research obtained the optimal time and cost using Time Cost Trade Off method with alternative additional 50% labor. The result of crash duration is less 74 days from actual schedule, with cost Rp.3.805.459.099,- there is a decreased of 13,58% or Rp.597.910.301,- from the actual duration fee of Rp.4.403.369.400,-. Comparison of flue stack progress using the S curve, it was found that the schedule with accelerated duration could be completed faster that the actual duration because the more sloping line indicated greater weekly progress